Utilization of Maggot Larvae (Hermetia illucens) for Processing Food Waste at the UIN Raden Intan Lampung Canteen - Listiana, Ika; Marlina, Marlina; Kuswanto, Eko; Hoya, Ade Lenty (Biology, Medicine, & Natural Product Chemistry, 2024)
Waste management using maggot larvae (Hermetia illucens) can be an innovative strategy for reducing organic waste. This study aims to determine the effectiveness of maggot larvae in processing organic waste at the UIN Raden Intan Lampung Canteen. The research used a Completely Randomized Design (CRD) technique with 3 treatments and 3 replications. The observed parameters were duration, residue, and maggot weight. The organic waste used included vegetables, fruits, rice, and bones. The results showed that for bone and rice waste, maggots were able to reduce waste by 80%, producing an average residue of 141.3 grams with a decomposition duration of 515 minutes and a final maggot weight of 320.67 grams. For fruit and vegetable waste, maggots reduced waste by 58%, producing an average residue of 293 grams with a decomposition duration of 395 minutes and a final maggot weight of 560.33 grams. For mixed waste, maggots reduced waste by 81% with a decomposition duration of 496.6 minutes and a final maggot weight of 430.3 grams.